Aromaticity of the most stable adenine and purine tautomers in terms of Hückel's 4N+2 principle. Issue 35 (30th August 2019) - Jezuita, Anna; Szatylowicz, Halina; Marek, Paulina H.; Krygowski, Tadeusz M.
Abstract: Electron structures of the fused rings in 7H and 9H tautomers of purine and adenine follow the 4N + 2 rule; the values of pEDA, HOMA, NICS and FLU indices document their aromatic character. In the 1H and 3H tautomers, these rings contain five or seven π electrons, hence they do not follow this rule and consequently exhibit lower aromaticity. This also applies to the aromaticity of whole molecules. Graphical abstract: Image 1 Highlights: A new view at the electronic structure of the most stable adenine and purine tautomers. Five- and six-membered rings either follow the Hückel 4N+2 rule (tautomers 7H and 9H) or do not (3H and 1H). Individual components (imidazole, pyrimidine) are more aromatic than when they are fused in adenine and purine molecules.